Diffuse large B-cell lymphoma in very elderly patients: Towards best tailored treatment – A systematic review. (April 2021) - Tavares, Alda; Moreira, Ilídia
Graphical abstract: Highlights: Treatment of elderly DLBCL patients represents a particular challenge. Most clinical trials exclude the octogenarian patients with DLBCL. Evidence favours R-miniCHOP treatment for very elderly fit patients. Less intensive regimens should be considered for very elderly unfit. Geriatric assessment is an important tool for selecting the best candidates to receive curative therapy. Abstract: Introduction: Diffuse large B cell Lymphoma (DLBCL) is a potentially curative lymphoma with increasing incidence with ageing. Treatment of elderly DLBCL patients represents a particular challenge due to their comorbidities and performance status. Methods: A search for original articles focused on the treatment of elderly DLBCL patients was performed in PubMed database and 633 were found and reviewed. Thirty-eight studies meeting our inclusion criteria were published since 2007. Results: Thirteen studies were retrospective and 25 phase II/III clinical trials. Most of them investigated the efficacy of dose-adjusted R−CHOP regimen. Alternative therapeutic drugs together with geriatric assessment were also evaluated. For fit patients aged 80 and over, the strongest evidence favours R-miniCHOP regimen. Conclusion: A dose-adjusted R−CHOP may be the recommended treatment in elderly DLBCL patients. New tools such as the Comprehensive Geriatric Assessment provide useful guidance for treatment choice, based on comorbidities and frailty index of this group.